Quantitative Study on the Effect of Age, Education, Experience, and Wages on Labor Productivity in Housing Projects - Prahara, Rahma Sandhi; Fauziyah, Nur Dinah; A’yuni, Diah Syifaul (Danadyaksa: Post Modern Economy Journal, 2025)
This study explores how age, education, experience, and wages affect labor productivity in the housing sector of Mojosari, Mojokerto Regency. With rapid urbanization and rising housing demand, understanding these factors is crucial for improving workforce performance. Using a quantitative approach and multiple linear regression, data was gathered from 150 construction workers in Mojosari through random sampling. The analysis found that all four factors—age, education, experience, and wages—significantly impact productivity. Education had the greatest influence, emphasizing the importance of skill development. Both experience and wages also positively affected productivity, while age showed a mixed effect, with productivity increasing until a certain age before declining. The model explained 62% of the productivity variation. The findings suggest the need for policies focusing on workforce training, fair wages, and better management to enhance productivity. Investing in education and skills development will be key for sustaining growth in the housing sector. This research provides valuable insights for improving labor productivity in Indonesia's housing industry, particularly in rapidly urbanizing areas.